STUDI EKONOMIS PENGGUNAAN PLTS ROOFTOP 3 KWP FRAMELESS WITH ON-GRID SYSTEM PADA PELANGGAN R/4400 VA - I Komang Widi Astawa; Ida Ayu Dwi Giriantari; I Wayan Sukerayasa (Program Studi Teknik Elektro UNUD, 2021)
PLTS is one of the renewable energy technologies sourced from sustainable energy,namely the sun. The potential for solar energy is quite good, making Bali one of the targets forthe energy mix. This research focuses on the production of PV mini-grid energy, savingelectricity costs and finding out whether it is profitable or not to invest in the location, especiallyin one of the SARBAGITA areas located in Perum Nuansa Jimbaran from an economic point ofview. The method used is an economic analysis of investment feasibility, with supportingindicators such as DF, NPV, BCR, DPP, LCC, COE and CRF by considering economic aspects.Yield of this study found that the selling price of PLTS power to PLN was IDR. 1,444.70/kWh,investment cost PLTS is IDR. 61,274,248, it can generate savings of IDR. 5,078,700/year andcumulative income for the 25th year is IDR. 109,341,618. Price sensitivity is very influential onthe cost of PV mini-grid revenue. COE at the energy selling price of IDR 2,888/kWh, can alsoshow the feasibility of the investment so that the investment can be said to be economicallyprofitable.